What's in a name and why it matters: A historical analysis of the relationship between state authority, vigilantism and penal power in South Africa - Super, Gail (Theoretical criminology, 2017)
This article aims to clarify the relationship between state authority, vigilantism and penal power. I ask how shifting political contexts shape the construction of the ‘vigilante' and the legitimation (or not) of vigilante violence. Based on a historical analysis of how the terms ‘vigilante', ‘vigilantism' and ‘mob justice' are used in mainstream discourse in South Africa the article tracks the political transformations that took place in the South African state in the late 1970s, the mid-1980s and post-1994. I use the term ‘precarious penality' to describe penality on the periphery—both geographically, in marginalized poor black townships—and symbolically, to denote spaces where the boundaries between what is ‘state' and what is not are blurred. Spaces of ‘precarious penality' pose specific problems for the liberal principles of due process and human rights that are enshrined in the South African Constitution but often distorted in practice.